Enhancing conceptual understanding in elementary mathematics through technology integration and socially responsive teaching - Siti Rodiyah Hida; Thahira Wahyuni W.K.E. Kalani; Yuniar Marhamah S. Ibrahim; Melan Septiani Babay; Angsi Pakaya; Ivana Manorek; Chairil Anaz Yusuf; Irvin Novita Arifin; Isnanto Isnanto (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: Elementary education is shaped by social contexts and learning environments that influence students’ academic development. Mathematics learning, particularly basic number operations, remains challenging due to abstract content and limited contextual instruction. Technology-based learning media offer an innovative approach to improving engagement, equity, and learning outcomes within diverse educational settings. Methods: This study adopted a qualitative case study approach to examine the integration of science and technology in elementary mathematics learning, particularly in teaching basic number operations. Data were collected through classroom observations and semi-structured interviews with the homeroom teacher to explore instructional strategies, learning dynamics, and the use of technology-based learning media. Findings: The findings indicate that students experienced significant difficulties in understanding basic number operations due to abstract content and limited interactive learning experiences. The integration of technology-based learning media, particularly interactive and visual digital tools, increased student engagement, motivation, and conceptual understanding of mathematics. Effective technology use, supported by appropriate infrastructure and teacher creativity, transformed mathematics learning into a more active, meaningful, and student-centered process. Conclusion: Based on these things, it can be concluded that teachers need to improve their competence in providing good pedagogy to students in the classroom. With the advancement of digitalization, it can be a solution and improve the learning process of students in mathematics subjects in elementary schools. Novelty/Originality of this article: This study offers original insight by situating technology-integrated mathematics learning within the social and educational environment of elementary classrooms, highlighting how teacher-driven digital pedagogy can address learning inequities and foster more inclusive, student-centered outcomes in line with interdisciplinary social–education perspectives.